TEACHING LISTENING SKILLS IN ENGLISH LANGUAGE LEARNING - Turgunova Rano, (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This paper investigates the importance of teaching listening skills in English language learning. Listening is a complex and active process that involves understanding spoken language, interpreting meaning, and responding appropriately. In modern pedagogy, listening is considered one of the most essential skills for developing communicative competence. However, it remains one of the most challenging aspects for learners due to various linguistic and psychological factors.